Pet Market. - Vogt, Oliver; Seiner, Tanja (Kassel : Kunsthochschule Kassel, 2016)
Albus, Volker ; Berger, Leo ; Bostan, Ayzit ; Enders, Charlotte ; Flötotto, Christof ; Funcke, Sven ; Guixé, Martí ; Hehl, Dominik ; Herdin, Chris ; Herzberg, Sophie ; Indra, Nathalie ; Knüppel, Silvia ; Kosoric, Max ; Luft, Dietrich ; Medicus, Christoph ; Meyer, Jennifer ; Pawelzyk, Sanne ; Schäfer, Peter ; Seeger, Corinna ; Val, Olaf ; Wahl, Katharina
Pet Market, Galerie Erstererster, Berlin, 13. - 20. Juni 2015
boek